The arbitration jurisdiction of independent administrative authorities as an alternative mechanism for settling disputes of an economic nature - BOUHABEL, Fayssal; TAHIR, Abdennacer (The International tax journal, 2026)
The Algerian legislator has enshrined a modern approach to economic regulation by assigning a range of powers previously exercised by the administration to independent administrative authorities. This reinforces the principles of specialization and independence, and keeps pace with the rapid transformations in the economic environment. Among the most prominent of these powers is arbitration, which enables certain authorities to adjudicate disputes between economic operators within the sector under their supervision. This allows for a swift and effective resolution that aligns with the technical nature of regulated activities. However, this jurisdiction remains subject to legal constraints that define its subject-matter and sectoral scope. It has not been granted to all independent administrative authorities, but rather is limited to those whose establishment law explicitly stipulates it. These bodies issue administrative decisions of a special nature, blending regulatory functions with quasi-judicial aspects, while remaining subject to judicial review. They are also obligated to respect the procedural guarantees afforded to economic operators, thus upholding the principle of legality and ensuring a balance between economic efficiency and the protection of rights.